Plant metallothionein domains: functional insight into physiological metal binding and protein folding (BIOCHIMIE, 2006)
Plant metallothioneins (MTs) differ from animal MTs by a peculiar sequence organization consisting of two short cysteine-rich terminal domains linked by a long cysteine-devoid spacer. The role of the plant NIT domains in the protein structure and functionality is largely unknown. Here, we investigate the separate domain contribution to the in vivo binding of Zn and Cu and to confer metal tolerance to CUP1-null yeast cells of a plant type 2 NIT (QsMT). For this purpose, we obtained three recombinant peptides that, respectively, correspond to the single N-terminal (N25) and C-terminal (C18) cysteine-rich domains of QsMT, and a chimera in which the spacer is replaced with a four-glycine bridge (N25-C18). The metal-peptide preparations recovered from Zn- or Cu-enriched cultures were characterized by ESI-MS, ICP-OES and CD and UV-vis spectroscopy and data compared to full length QsMT. Results are consistent with QsMT giving rise to homometallic Zn- or Cu-MT complexes according to a hairpin model in which the two Cys-rich domains interact to form a cluster. In this model the spacer region does not contribute to the metal coordination. However, our data from Zn-QsMT (but not from Cu-QsMT) support a fold of the spacer involving some interaction with the metal core. On the other hand, results from functional complementation assays in endogenous MT-defective yeast cells suggest that the spacer region may play a role in Cu-QsMT stability or subcellular localization. As a whole, our results provide the first insight into the structure/function relationship of plant MTs using the analysis of the separate domain abilities to bind physiological metals. (c) 2005 Elsevier SAS. All rights reserved.

Plant metallothionein domains: functional insight into physiological metal binding and protein folding - Domenech, Jordi; Mir, Gisela; Huguet, Gemma; Capdevila, Merce; Molinas, Marisa; Atrian, Silvia (BIOCHIMIE, 2006)
Plant metallothioneins (MTs) differ from animal MTs by a peculiar sequence organization consisting of two short cysteine-rich terminal domains linked by a long cysteine-devoid spacer. The role of the plant NIT domains in the protein structure and functionality is largely unknown. Here, we investigate the separate domain contribution to the in vivo binding of Zn and Cu and to confer metal tolerance to CUP1-null yeast cells of a plant type 2 NIT (QsMT). For this purpose, we obtained three recombinant peptides that, respectively, correspond to the single N-terminal (N25) and C-terminal (C18) cysteine-rich domains of QsMT, and a chimera in which the spacer is replaced with a four-glycine bridge (N25-C18). The metal-peptide preparations recovered from Zn- or Cu-enriched cultures were characterized by ESI-MS, ICP-OES and CD and UV-vis spectroscopy and data compared to full length QsMT. Results are consistent with QsMT giving rise to homometallic Zn- or Cu-MT complexes according to a hairpin model in which the two Cys-rich domains interact to form a cluster. In this model the spacer region does not contribute to the metal coordination. However, our data from Zn-QsMT (but not from Cu-QsMT) support a fold of the spacer involving some interaction with the metal core. On the other hand, results from functional complementation assays in endogenous MT-defective yeast cells suggest that the spacer region may play a role in Cu-QsMT stability or subcellular localization. As a whole, our results provide the first insight into the structure/function relationship of plant MTs using the analysis of the separate domain abilities to bind physiological metals. (c) 2005 Elsevier SAS. All rights reserved.
The following values have no corresponding Zotero field: pub-location: 23 RUE LINOIS, 75724 PARIS, FRANCE publisher: ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER
Keywords: Cu-aggregates; metallothionein; MT dimers; Quercus suber; separate Cys-rich domains; spacer region; yeast complementation; Zn-aggregates